Orphan Drug Regulation: A missed opportunity for children and adolescents with cancer. (October 2017) - Vassal, Gilles; Kearns, Pam; Blanc, Patricia; Scobie, Nicole; Heenen, Delphine; Pearson, Andy
Abstract: Background: Oncology represents a major sector in the field of orphan drug development in Europe. The objective was to evaluate whether children and adolescents with cancer benefited from the Orphan Drug Regulation. Methods: Data on orphan drug designations (ODDs) and registered orphan drugs from 8th August 2000 to 10th September 2016 were collected from the Community Register of medicinal products for human use. Assessment history, product information and existence of paediatric investigation plans were searched and retrieved from the European Medicine Agency website. Results: Over 16 years, 272 of 657 oncology ODDs (41%) concerned a malignant condition occurring both in adults and children. The five most common were acute myeloid leukaemia, high-grade glioma, acute lymphoblastic leukaemia, graft-versus-host disease and soft-tissue sarcomas. 74% of 31 marketing authorisations (MAs) for an indication both in adults and children (26 medicines) had no information for paediatric use in their Summary of Product Characteristics (SmPC) at the time of the first MA. Furthermore, 68% still have no paediatric information in their most recently updated SmPC, at a median of 7 years after. Only 15 ODDs (2%) pertained to a malignancy occurring specifically in children and only two drugs received an MA: Unituxin for high-risk neuroblastoma and Votubia for sub-ependymal giant-cell astrocytoma. Conclusion: The Orphan Drug Regulation failed to promote the development of innovative therapies for malignancies occurring in children. Major delays and waivers occurred through the application of the Paediatric Medicines Regulation. The European regulatory environment needs to be improved to accelerate innovation for children and adolescents dying of cancer. Highlights: The Orphan Drug Regulation failed to promote the development of innovative therapies for children and adolescents with cancer. Only two orphan medicines approved for the treatment of malignancies occurring specifically in children over 16 years. Two-third of orphan medicines approved for a cancer occurring in adults and children do not have any pediatric information. The EU regulatory environment needs to be improved to accelerate innovation for children and adolescents dying of cancer.